Experiences of treatment-resistant mental health conditions in primary care: a systematic review and thematic synthesis - Talbot, AC; Lee, C; Roberts, N; Ryan, S; Mahtani, K; Albury, C (BioMed Central, 2022)
Background: Most adults fail to achieve remission from common mental health conditions based on pharmacological treatment in primary care alone. There is no data synthesising the reasons. This review addresses this gap through a systematic review and thematic synthesis to understand adults' experiences of using primary care for treatment-resistant mental health conditions (TRMHCs). We use the results to produce patient-driven recommendations for better support in primary care.